Uji Sitotoksik Kapang Laut Perairan Nipah Terhadap Artemia salina Leach - Elrade Rofaani; Reni Nur'aini Adiati (Jurnal Perikanan Universitas Gadjah Mada, 2007)
Test on cytotoxic activity of marine fungi from Nipah waters have been conducted. Each solate was cultured on malt extract liquid for 15 days, and extracted by using ethyl acetate to both pellet and supernatant. Brine Shrimp Lethality Test (BSLT) was applied for cytotoxic test against Artemia salina Leach at concentrations of 10; 100; 500; and 1000 μg/ml. Cytotoxic activity showed that the percentage mortality of the brine shrimp was obtained by 1000 μg/ml at 75-100%, and the LC50 of each extract was varied from 117.21 to 531.65 μg/ml. Furthermore, the lowest LC50 was showed by sample with code number NA 14.3 at 117.21 μg/ml.